Monitoring the Residues of Some Phpsphorous Pesticides in Water and Milk from Abu Jarash Farms (Damascus University Journal of agriculture sciences, 2022)
In this research, the exposure of water wells in vegetables fields in Abu – Jarash to the commonly used insecticides (chlorpyrifos, methyl parathion, dimethoate and methamidavos) from the organic phosphorous group was evaluated. Water samples were obtained during winter and summer. Samples were extracted and residues were estimated by gas chromatography which attached to the unit mass (GC-Ms) and were studied some physical and chemical properties of the collected water samples. The results showed that water samples which were collected from the two wells under study contain traces of dimethoate and chlorpyrifos residues in February. Whereas, the residues of the chlorpyrifos pesticide were found in July and dimethoate in June was found at concentration less than permissible limits for water pollution. Also, the pollution of milk which was obtained from cows from Abu Jerash farms with chlorpyrifos and dimethoate was studied during winter and summer seasons. The results showed that the collected milk samples showed traces of the two pesticides residues in February, while the residues of chlorpyrifos appeared in the milk samples collected in July and June at concentrations (0.005 ± 0.025 and 0.002 ± 0.019 mg / kg), respectively. Dimethoate in June at a concentration of (0.007 ± 0.044 mg / kg) and in July in the form of traces. These values are below the maximum permissible values of the FAO dome.
Keywords: Pesticides residues; water; milk; GC-MAS